2004
DOI: 10.1093/hmg/ddh282
|View full text |Cite
|
Sign up to set email alerts
|

Mild overexpression of MeCP2 causes a progressive neurological disorder in mice

Abstract: Mutations in the X-linked methyl-CpG-binding protein 2 (MECP2), encoding a transcriptional repressor, cause Rett syndrome and a variety of related neurodevelopmental disorders. The vast majority of mutations associated with human disease are loss-of-function mutations, but precisely what aspect of MeCP2 function is responsible for these phenotypes remains unknown. We overexpressed wild-type human protein in transgenic mice using a large genomic clone containing the entire human MECP2 locus. Detailed neurobehav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
592
3
7

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 550 publications
(638 citation statements)
references
References 54 publications
36
592
3
7
Order By: Relevance
“…12 designed to include BAC clones for MECP2, based on the observation that increased MECP2 levels cause progressive neurologic features in a mouse model. 33,34 CMA detection of MECP2 duplications was demonstrated on our initial patients 1 and 2, along with their asymptomatic mothers, using our version 4 microarray (366 FISH-verified BAC clones). 27 Figure 2A shows representative CMA data from patient 1, which was cohybridized with a normal male genome; the results show a twofold increased copy number of the two Xq28 genomic clones on the CMA version 4 microarray (i.e., BAC RP11-119A22 including MECP2, and RP11-24410 including the flanking L1CAM gene).…”
Section: Mecp2 Gene Duplications In Male Patientsmentioning
confidence: 84%
See 2 more Smart Citations
“…12 designed to include BAC clones for MECP2, based on the observation that increased MECP2 levels cause progressive neurologic features in a mouse model. 33,34 CMA detection of MECP2 duplications was demonstrated on our initial patients 1 and 2, along with their asymptomatic mothers, using our version 4 microarray (366 FISH-verified BAC clones). 27 Figure 2A shows representative CMA data from patient 1, which was cohybridized with a normal male genome; the results show a twofold increased copy number of the two Xq28 genomic clones on the CMA version 4 microarray (i.e., BAC RP11-119A22 including MECP2, and RP11-24410 including the flanking L1CAM gene).…”
Section: Mecp2 Gene Duplications In Male Patientsmentioning
confidence: 84%
“…These patient findings are consistent with data from transgenic mouse models overexpressing the wild-type human MECP2 protein. 33,34 These mice appear clinically normal at birth but develop Rett-like progressive neurologic problems including motor dysfunction, hypoactivity, tremors, and ataxia, and die prematurely. 33 Higher MECP2 protein levels were found to correlate with more severe phenotypes in these mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, changes in DNA methylation can affect levels of histone acetylation (Becker et al, 1987;Collins et al, 2004;Cross et al, 1997;Jones et al, 1998;Nan et al, 1997Nan et al, , 1998 and we have demonstrated in vitro that DNMT inhibition significantly attenuates PKC-induced H3 acetylation (Levenson et al, 2006). Therefore, we hypothesized that the blockade of memory consolidation by 5-AZA could be partially due to modulation of histone acetylation.…”
mentioning
confidence: 98%
“…One NID mutation, R306C, causes a severe RTT-like phenotype in mice (13,15,16). Moreover, mouse models of MeCP2 duplication syndrome suggest that both the MBD and the NID must be intact for this adverse molecular pathology to develop (16,17).…”
mentioning
confidence: 99%